Pemasaran UMKM Desa Sei Simpang Dua Melalui E-Commerce - Hafsari, Rizka; Arribe, Edo; Diansyah, Risnal; Mulyana, Wide; Aryanto; Setiawan Ardi Wijaya (PT. Banjarese Pacific Indonesia, 2024)
This service focuses on MSMEs in Sei Simpang Dua Village, Kampar Regency, Kampar Kiri Hilir District, Riau Province. The purpose of this service is to meet customer needs and make it easier for MSME (Micro, Small and Medium Enterprises) players to disseminate information related to products in the village, as well as support government programs, namely smart villages and be able to face the Industrial Revolution 4.0, namely the importance of digital transformation with a vision towards village digitalization. This service method includes observation, training, monitoring and evaluation. So that the results of this service are in the form of utilizing e-commerce applications that have been built for the village of sei simpang dua with 3 menus including the home menu, product menu and basket menu. The home menu contains general information, the product menu displays all products from the village of sei simpang dua and the basket menu displays the number of items and the total shopping price.